2020
DOI: 10.1186/s12904-020-00553-w
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods investigation of end-of-life surrogate decisions among older adults

Abstract: Background: A large number of end-of-life decisions are made by a next-of-kin for a patient who has lost their decision-making capacity. This has given rise to investigations into how surrogates make these decisions. The experimental perspective has focused on examining how the decisions we make for others differ from our own, whereas the qualitative perspective has explored surrogate insights into making these decisions. Methods: We conducted a mixed methods study to bring these two perspectives together. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…3,4 However, many scholars have argued that family members cannot correctly predict their elderly's preferences for end-of-life care. [5][6][7][8] A cohort study that included 363 patient-surrogate dyads showed that nearly half (46.6%) of the patients had at least one medical treatment or code status order that was out of accordance with the goal of care recognized by their surrogates. 9 A Taiwanese study surveyed 100 dyads of hospitalized elderly individuals and their caregivers and found the consistency was 42.28% for preferences of end-of-life medical care between elderly individuals and caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, many scholars have argued that family members cannot correctly predict their elderly's preferences for end-of-life care. [5][6][7][8] A cohort study that included 363 patient-surrogate dyads showed that nearly half (46.6%) of the patients had at least one medical treatment or code status order that was out of accordance with the goal of care recognized by their surrogates. 9 A Taiwanese study surveyed 100 dyads of hospitalized elderly individuals and their caregivers and found the consistency was 42.28% for preferences of end-of-life medical care between elderly individuals and caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, as previously discussed, surrogates' reports of prior engagement in discussions of end-of-life preferences with their partners predicted greater accuracy on the cardiac bypass decision vignette. This relation corroborates prior findings that such discussions tend to improve surrogates' decision making, as measured both by surrogates' self-reported ease with decision making and the accuracy of the decisions they made when compared to those of their partners (e.g., Batteux, Ferguson, & Tunney, 2020). Similar to relations observed for the mechanical ventilation vignette, greater empathy and perceived similarity to patients on end-of-life values was associated with an increased likelihood of agreement on the cardiac bypass decision.…”
Section: Variables Related To Accuracy On Individual Decision Vignettessupporting
confidence: 88%
“…The discrepancy in treatment decisions between patients and surrogates is particularly alarming given that surrogates reported that they felt they understood the costs and benefits related to the vignettes relatively well, and that they had discussed end-of-life preferences with patients to some extent. Prior research has documented a propensity for surrogates to reflect that they feel more equipped to make decisions when they have discussed patients' preferences in advance (e.g., Batteux, Ferguson, & Tunney, 2020;Schenker et al, 2012). Engaging in prior discussions may be associated with improved accuracy in some cases, but not all.…”
Section: Surrogates' Accuracy On Decision Vignettesmentioning
confidence: 99%
“…The discrepancy in treatment decisions between patients and surrogates is particularly alarming given that surrogates reported that they felt they understood the costs and benefits related to the treatments relatively well, and that they had discussed end-of-life preferences with patients to some extent. Prior research documents a propensity for surrogates to feel more equipped to make decisions when they have discussed patients’ preferences in advance (e.g., [3] ).…”
Section: Discussionmentioning
confidence: 99%